In-situ electric field induced nanoscale BO6 octahedral tilting in lead-free Fe-doped 0.95(Na1/2Bi1/2)TiO3–0.05BaTiO3 single crystal. (May 2019) - Xue, Saidong; Luo, Haosu; Zhao, Xiangyong; Wang, Feifei; Lin, Di; Deng, Hao; Li, Xiaobing; Yue, Qingwen; Tang, Yanxue; Fang, Bijun; Zhang, Haiwu
Abstract: The phase transition process of pure and 0.5 at% Fe-doped 0.95(Na1/2 Bi1/2 )TiO3 –0.05BaTiO3 (NBBT5) single crystals under in-situ electric-field was investigated using the Raman spectroscopy. The pure NBBT5 exhibited R 3c (a − a − a − octahedral tilting) symmetry when subjected to an external electric field ( E ) up to 70 kV/cm. While after the Fe-doping, the crystal underwent a transition from P 4bm (a 0 a 0 c + octahedral tilting) to P 4mm (a 0 a 0 c 0 octahedral tilting) phase under E of 30–40 kV/cm. The results indicated that the octahedral tilting in the Fe-NBBT5 was substantially suppressed by the electric field, which was suggested to contribute to the enhanced piezoelectric response compared to the pure one. Graphical abstract: Unlabelled Image